Analisis Laporan Realisasi Anggaran Dinas Pemberdayaan Masyarakat dan Gampong Kabupaten Aceh Barat - Susi Susanti (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This research intends to find out the realization of the budget of the Aceh Barat Community Empowerment and Gampong Office. The research procedure used is using quantitative descriptive procedures. The type of data used is secondary data obtained from financial statements through documentation techniques. The analytical method used is a comparison ratio, namely the ratio of efficiency and effectiveness ratio. The results of the research prove that the level of effectiveness of the financial performance of the Aceh Barat Community and Gampong Empowerment Service in 2019 is said to be effective, in 2020 it is considered effective, and in 2021 it is said to be quite effective. Thus, the realization of the budget at the West Aceh Community Empowerment and Gampong Service can be said to have been right on target in accordance with the work program for the 2019-2021 period.